Persepsi Masyarakat Samarinda Terhadap Ambang Batas Pencalonan Presiden Dalam Pemilihan Umum Di Indonesia - Dimas Budi Prasetyo; Muhammad Hairul Saleh (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
This research was conducted in Samarinda City, Samarinda Regency, East Kalimantan, the purpose of this study is to find out how the perception of the people of samarinda on the presidential thresold for presidential candidacy in the general election in Indonesia, as well as to find out what factors influence the perception of the people of Samarinda. This research is descriptive qualitative using the miles and huberman model by reducing data, presenting data and conclusions. In this study, the authors used observation, interview and documentation methods. Based on the results of research on the perception of the people in Samarinda on presidential thresold candidacy in general election in Indonesia, people has diverse views, but in general people’s view can be grouped into two groups. Community groups that support the requirement and community groups that reject the thresold requirement. Then related to factors that influence people’s perception of the thresold for presidential candidacy, researchers found three factors. First, the important factor. Second, the experience factor. Third, the expectation factor.